Caregiver Experiences, Healthcare Provider Perspectives and Child Outcomes with Virtual Care in a Neonatal Neurodevelopmental Follow-Up Clinic: A Mixed-Methods Study - Kamini Raghuram; Hayle Noh; Seungwoo Lee; Nicole Look Hong; Edmond Kelly; Vibhuti Shah (MDPI AG, 2024)
Background: Caregiver and healthcare provider perspectives of virtual care have not been explored in depth in the literature for neonatal follow-up clinics. Our objective was to evaluate caregivers' and healthcare providers' perspectives and compare neurodevelopmental outcomes of preterm neonates before and after implementing virtual care during the SARS-CoV-2 pandemic. Methods: Semi-structured interviews were conducted with families and healthcare providers, designed and analyzed using phenomenological qualitative methods. A retrospective cohort study was conducted to evaluate and compare neurodevelopmental characteristics of two preterm cohorts, one before ("in-person") and after ("virtual") virtual care. Results: Three themes were identified: increased confidence in in-person assessments, adequate delivery of information using virtual platforms and a preference for specialized care through the neonatal follow-up clinic. A total of 252 infants born preterm, 104 infants in the in-person group and 148 infants in the virtual group, were included in the study. The adjusted odds ratio (aOR) of cerebral palsy was lower when virtual care was used compared to in-person assessments (aOR = 0.11, 95% CI 0.01-0.98) while the adjusted odds of cognitive delay measured by in-person standardized testing were higher (aOR = 2.78, 95% CI 1.25-6.19). Conclusions: Caregivers and healthcare providers prefer in-person assessments for comprehensive developmental support. It may be more challenging to detect subtle cognitive differences using caregiver-reported measures. Cerebral palsy may be missed when assessments are completed virtually.